2016
DOI: 10.1002/lno.10268
|View full text |Cite
|
Sign up to set email alerts
|

Giant ice rings on lakes Baikal and Hovsgol: Inventory, associated water structure and potential formation mechanism

Abstract: Observations of giant ice rings on Lake Baikal (Russia) have recently sparked scientific and public interest. However, there is still no clear consensus on their origins. Here, we provide an inventory of the ice rings based on satellite imagery and photography for 1974-2014. We have identified 45 rings on Lake Baikal (compared with 13 previously known) and also for the first time four rings for the neighbouring Lake Hovsgol (Mongolia). The results of our hydrographic surveys beneath the ice rings in Lake Baika… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
47
0
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 17 publications
6
47
0
5
Order By: Relevance
“…No ice rings have been observed in 2017 for Lake Baikal and no new ice rings for Lake Hovsgol. However, we have also discovered ice rings in a new water body—Lake Teletskoye (Kouraev et al , c , d ; Leech ).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…No ice rings have been observed in 2017 for Lake Baikal and no new ice rings for Lake Hovsgol. However, we have also discovered ice rings in a new water body—Lake Teletskoye (Kouraev et al , c , d ; Leech ).…”
Section: Resultsmentioning
confidence: 89%
“…Our hydrographic surveys beneath the ice rings in Lake Baikal in 2012–2014 and in Lake Hovsgol in 2015 have shown the presence of warm lens‐like (double‐convex form) eddies before and during the manifestation of ice rings (Kouraev et al ). We have shown that giant ice rings are a surface manifestation of these intrathermocline lens‐like eddies.…”
mentioning
confidence: 94%
“…For example, a review on the under‐ice microbiome by Bertilsson et al () has been cited 25 times according to Google Scholar. Other recent examples include research on ice phenology (Arp et al ; Van Cleave et al ; Beyene and Jain 2015), under‐ice physical limnology (Forrest and Jain ; Rizk et al ; Salonen et al ; Titze and Austin 2014; Bruesewitz et al ; Steel et al ; Kouraev et al ), and under‐ice primary production (Hawes et al ; Katz and Austin ). In addition, there has been a clear surge of research on biogenic gas production and carbon cycling under ice (e.g., Ducharme‐Riel et al ; Denfeld et al 2016), likely built upon the work of Striegl et al () on potential gas emissions measured during ice cover, Karlsson et al (2008) on under‐ice respiration, and Cole et al () on lakes within the global carbon cycle, among others.…”
Section: Winter Research Historically Left Out In the Coldmentioning
confidence: 99%
“…For example, a review on the under-ice microbiome by Bertilsson et al (2013) has been cited 25 times according to Google Scholar. Other recent examples include research on ice phenology (Arp et al 2013;Van Cleave et al 2014;Beyene and Jain 2015), under-ice physical limnology (Forrest and Jain 2013;Rizk et al 2014;Salonen et al 2014;Titze and Austin 2014;Bruesewitz et al 2015;Steel et al 2015;Kouraev et al 2016), and under-ice primary production (Hawes et al 2014;Katz and Austin 2015). In addition, there has been a clear surge of research on biogenic gas production and carbon cycling under ice (e.g., Ducharme-Riel et al 2015;Denfeld et al 2016), likely built upon the work of Striegl et al (2001) on potential gas emissions measured during ice cover, Karlsson et al (2008) on under-ice respiration, and Cole et al (2007) on lakes within the global carbon cycle, among others.…”
Section: Winter Research Historically Left Out In the Coldmentioning
confidence: 99%